Artificial intelligence in the service of man: medical, social and economic aspects - Svetlana Gennadevna Karamysheva (Laplage em Revista, 2021)
Artificial intelligence (AI) and robotic technologies have recently been increasingly used in various areas of human activity. Thus, the purpose of this paper is to consider the medical, social and economic aspects of the use of artificial intelligence in various spheres of human activity. The reason for people turning to the above-mentioned innovations is to expand a number of human capabilities, increase labor productivity, reduce the negative impact of the human factor, etc. The social aspect of the use of robotic technologies should also not be underestimated. The economic aspects of the use of artificial intelligence and robotic technologies are the possibility of optimizing the number of labor resources, replacing a whole staff of auxiliary workers, which can significantly reduce the salary fund in general and the costs of a company using such technologies, in particular.